PEMANFAATAN BATUBARA SEBAGAI BAHAN BAKAR ALTERNATIF UNTUK PENGERINGAN KARET REMAH PADA INDUSTRI KARET - Agus Mirwan; Doni Rahmat Wicakso (INFO-TEKNIK, 2004)
The scarcity of diesel fuel in the future especially for drying rubber is based on some statements which said that the use of fuel in Indonesiawill increase along with the decrease oil reserve and also with the decrease subsidy. Early efforts have been made to obtain an alternative fuel to substitute diesel fuel as an anticipation step to face the problems that will be a barrier to the continuity of rubber production. Rubber is one of the main commodities from the agricultural sector in Indonesia. According to the thought above, a research has been done to use raw coal as an alternative fuel for drying crumb rubber. This research was done in the crumb rubber factory in Kalimantan. The burner used is Cycloburner made by Water Wide Guthrie, Malaysia-New Zealand. Drying temperature for SIR 10 is 115-120oC. Raw coal used is Adaro-Kalimantan type.The result shows that the gas from the combustion of the raw coal does not affect the rubber quality. The rubber fulfills the requirements as SIR 10 with dirt content 0.03 - 0.049%, ash content 0.37 - 0.48%, volatile matter 0.34 - 0.38%, Po 39 - 48.5 and PRI 70.5 - 76.7.